GOLD MINING BY THE METHODS OF GEOTECHNOLOGY: TECHNOLOGICAL DECISIONS - Ptitsyn A.B. (My University, 2001)
The geotechnology is defined as a mining method of nonferrous, rare and noble metals by their selective solution with the help of chemical reactants at the deposition place and the following extraction of the chemical compounds formed in the reaction zone. The general characteristic of the geotechnological methods of metal mining is given and their advantages over the traditional methods are shown. The main technological decisions used in different countries in gold mining by the methods of geotechnology are reviewed.